Monte Carlo Simulation of the TAIGA Experiment - Postnikov, E. B.; Astapov, I. I.; Gafarov, A. R.; Garmash, A. Yu.; Gorbunov, N. V.; Grebenyuk, V. M.; Gress, O. A.; Gress, T. I.; Grishin, O. G.; Grinyuk, A. A.; Horns, D.; Ivanova, A. L.; et al. (Bulletin of the Russian Academy of Sciences: Physics, 2019)
The TAIGA (Tunka Advanced Instrument for cosmic ray physics and Gamma-ray Astronomy) experiment aims at observing gamma-rays in the energy range from 1 TeV to several 100 TeV. The operation of the observatory is based on a new hybrid approach that combines imaging air Cherenkov telescopes (IACTs) and wide-angle Cherenkov detectors (TAIGA-HiSCORE) for measuring times of extensive air shower (EAS) light front arrival. Monte Carlo simulations are compared to real data to determine the performance of the detector setup. Dedicated software and algorithms are described, model parameters are given, and an overview of the current status of model-based performance studies is presented.